Role of eddies in structuring the mesozooplankton composition in coastal waters of the western Bay of Bengal. (October 2019) - Jagadeesan, L.; Kumar, G. Sampath; Rao, D.N.; babu, N. Surendra; Srinivas, T.N.R.
Highlights: Hydrographical parameters were significantly differed between eddy phases. Core eddy subsurface was cool, nutrient rich and less oxygenated than the pre-eddy. Pre-eddy copepods are coastal forms and Poecilostomatoids dominance over calanoids. Mixture of coastal, oceanic, OMZ tolerant species were found in core eddy phase. Eddy trapped biological communities were retained in core eddy over long period. Abstract: The mesozooplankton community structure of a cold core eddy, moving through a coastal location (Bheemunipatnam) in the western Bay of Bengal (BoB), was studied continuously for 17 days (21st February to 8th March 2016) during Spring Intermonsoon. Vertical profiles of temperature, salinity and Chlorophyll a were measured in 1hr interval. Nutrients and dissolved oxygen were measured in every 3 hrs from 8 discrete depths. Mesozooplankton samples were collected through vertical haul (100 m depth to the surface) in 6 hrs intervals. Cluster analysis delineated the entire sampling days into 3 clusters based on temperature, salinity, anomaly of temperature and salinity in various depth layers Viz., phase I (Pre-eddy: 21st to 24th February), phase II (Core eddy: 28th February to 6th March) and phase III (Transition: 25th to 27th February and 7th to 8th March). The phase I was characterised as a comparatively warm, low saline, less nutrient and oxygenated subsurface water. During phase II, cool, nutrient-rich and oxygen deficient waters in the study location indicating the presence of a cold core eddy. Phase III is an intermediate condition between the phases I and II. Deep chlorophyll maxima (DCM) were shoaled to 23 m in Phase II from a depth of 38 m in Phase I. Mesozooplankton abundance was high during phase II (62320 No. m −2 ) compared to phase III (41633 No. m −2 ) and phase I (39510 No. m −2 ). Altogether 64 copepod species were identified of which, seven were dominant throughout the observation. Twelve species found as the indicator species in the core eddy condition. The high abundance of the Temora turbinata (upwelling indicator), Pleuromamma indica (low oxygen tolerant and highly central BoB reported) and occurrence of oceanic, oxygen minimum zone (OMZ) reported forms as indicator species in phase II is indicative of their entrainment from offshore by eddies. Eddy genesis and their movement tracking appear that this northeastern offshore formed cold core eddy advected to western coastal Bay of Bengal and traversing through the study site during the sampling period. Copepod species composition indicates the eddy trapped biological communities were sustained and retained in the core over a long period, and it advected over a long distance. This study is the first kind of information about northeastern offshore formed cold core eddy carries the plankton community in coastal waters of western BoB on their path and explains copepods community structure can be used as the indicator of eddy water masses.